THE MAIN GENDER CHARACTERISTICS IN MANAGEMENT - Munarova , Rano; Shirinova, Zarnigor; Khujakulova , Mokhinabonu (MMIT Proceedings, 2023)
The article deals with the problem of studying gender characteristics and management styles. Gender is defined as a social status that determines individual opportunities in education, professional activity, access to power, sexuality, family role and reproductive behavior.